Does Individual Placement and Support satisfy the users` needs? - Sandra eViering; Matthias eJaeger; Carlos eNordt; Franziska eBühler; Bettina eBärtsch; Hansjörg eLeimer; Peter eSommerfeld; Wulf eRössler; Wolfram eKawohl (Frontiers Media S.A., 2015)
This study aims to investigate clients' satisfaction with Individual Placement and Support (IPS) at the University Hospital for Psychiatry Zurich (PUK). Furthermore this study aims to investigate if clients feel the approach of IPS as a useful approach to fulfill their needs. 125 people were recruited from one of the three IPS services of PUK and were asked to complete a structured questionnaire. The following IPS services were available: i) randomized controlled trial ZHEPP (www.zhepp.ch), ii) randomized controlled trial ZInEP (www.zinep.ch) and iii) us clinical SE service of PUK (IPS-PUK). The clients mostly indicated that the IPS was generally useful and fitted their needs. Overall satisfaction of the participants with the IPS services of PUK was very high. Furthermore, this study confirms that client satisfaction and symptom severity are associated. In conclusion, participants of the IPS services received the support they were looking for. This means that the approach of IPS fits the needs of different patient groups and can be used without any modifications. The most important limitation is the unequal group sizes. Therefore, the obtained results need to be strengthen by future research.